A Combined Nutrition and Exercise Intervention Influences Serum Vitamin B-12 and 25-Hydroxyvitamin D and Bone Turnover of Healthy Chinese Middle-Aged and Older Adults. Issue 8 (26th June 2020) - Groenendijk, Inge; Chan, Ruth; Woo, Jean; Ong, Sherlin; Parikh, Panam; Bragt, Marjolijn C E; de Groot, Lisette C P G M
ABSTRACT: Background: Hong Kong faces several public health problems including malnutrition and osteoporosis. Considering the typical Chinese diet and overall low physical activity levels of Chinese adults, timely interventions to improve nutritional status and bone health are needed. Objectives: We examined the effects of a nutrition plus exercise intervention on serum vitamin B-12 and 25-hydroxyvitamin D [25(OH)D], bone turnover markers, and parathyroid hormone (PTH) concentrations in apparently healthy Chinese middle-aged and older adults. Methods: In this 24-wk randomized controlled trial, 180 Chinese adults (85 women, mean ± SD age: 61 ± 6 y) were randomly assigned to receive a fortified milk supplement (2 × 30 g/d) and an exercise program (2 × 1 h/wk including resistance, balance, and aerobic training) or no intervention. The primary outcome was physical performance. In this article we analyzed the secondary outcomes serum vitamin B-12 and 25(OH)D concentrations, assessed at baseline, 12 wk, and 24 wk. Also, bone turnover markers and PTH concentrations were studied. Linear mixed models evaluated group differences over time. Results: A significant time × group interaction ( P < 0.001) was found for serum vitamin B-12 and 25(OH)D concentrations and the bone turnover markers, but not for serum PTH concentrations ( P = 0.09). The intervention increased mean ± SD vitamin B-12 concentrations from baseline (345 ± 119 pmol/L) to 24 wk (484 ± 136 pmol/L), whereas concentrations remained stable within the control. For 25(OH)D concentrations, the intervention group had a greater increase from baseline (54.7 ± 14.2 nmol/L) to 24 wk (80.1 ± 19.2 nmol/L) than the control (60.6 ± 15.2 compared with 65.6 ± 14.6 nmol/L). The ratio of the net effect of bone formation and resorption was greater in the intervention group, suggesting less bone remodeling, irrespective of sex. Conclusions: A fortified milk supplement and exercise intervention successfully improved vitamin B-12 and 25(OH)D concentrations as well as the balance of bone turnover markers of Chinese middle-aged and older adults. This trial was registered at trialregister.nl as NTR6214.